Therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy: temperature control during transport - Sofia O. Correia; André M. Graça; Isabel Sampaio; Carlos Moniz; Maria do Céu Machado (Hygeia Press di Corridori Marinella, 2016)
This study aims to assess the adequacy of temperature control during transport of patients referred for therapeutic hypothermia at our centre and to evaluate the occurrence of complications when temperature control is not adequate. Transport data of patients (n = 37) referred during a period of 30 months was reviewed retrospectively, as well as our prospectively collected database of infants treated with hypothermia. We evaluated duration of transport, incidence of excessive cooling on admission and associated complications. Distance from the referring hospital and duration of the transport were not associated with excessive cooling. We then divided patients into two groups according to adequacy of temperature control during transport depending on the presence or absence of regular temperature recordings and compared study variables between the groups. A significant correlation was found between the lack of adequate temperature records during transport (n = 19) and excessive hypothermia on admission (42% vs. 11% for the group with adequate temperature monitoring). There was a trend towards increased incidence of coagulation problems for infants who had admission temperatures below 32.0°C. Passive cooling is simple and effective to ensure early achievement of neuroprotective temperature, but continuous temperature monitoring during transportation is mandatory in order to avoid excessive cooling.